(untitled) (Analysis in Theory and Applications, 2022)
In the present paper, we prove the 12-Hölder continuity of spectral measures for the C^k Schrödinger operators. This result is based on the quantitative almost reducibility and an estimate for the growth of the Schrödinger cocycles in [5].